Escalante's dream on the trail of the Spanish discovery of the Southwest - Roberts, David 1943-2021 (W. W. Norton & Company, 2019)
In July 1776 a pair of Franciscan friars, Francisco Atanasio Domínguez and Silvestre Vélez de Escalante, were charged by the governor of New Mexico with discovering a route across the unknown Southwest to the new Spanish colony in California. They had other goals as well, some of them secret: converting the indigenous natives along the way to the true faith, discovering a semi-mythical paradise known as Teguayó, hunting for sources of gold and silver, and paving the way for Spanish settlements from Santa Fe to Monterey. In strict terms, the expedition failed. Running out of food and beset by an early winter, the twelve-man team gave up in what is now western Utah. The retreat to Santa Fe became an ordeal of survival. The men were reduced to eating their own horses while they searched for a crossing of the raging Colorado River in Glen Canyon. Seven months after setting out, Domínguez and Escalante staggered back to Santa Fe. Yet in the course of their 1,700-mile voyage, the explorers discovered more land unknown to Europeans than Lewis and Clark would encounter a quarter-century later. Other writers, using Escalante's brilliant and quirky diary as a guide, have retraced the expedition route, but David Roberts is the first to dig beneath its pages to question and ponder every turn of the team's decision-making and motivation. Roberts weaves the personal and the historical narratives into a gripping journey of discovery through the magnificent American Southwest. --Publisher
Keywords: Domínguez, Francisco Atanasio -- ca. 1740-1805; Vélez de Escalante, Silvestre -- 1749-1780; Geschichte 1776; Indigenes Volk; Mission; Erforschung; USA -- Südweststaaten; Domínguez-Escalante Expedition / (1776); Roberts, David / 1943- / Travel / Southwest, New; Domínguez, Francisco Atanasio / active 1776; Vélez de Escalante, Silvestre / -1792; Franciscans / Southwest, New / Biography; Roberts, David / 1943-; Franciscans; Domínguez-Escalante Expedition; Southwest, New / Description and travel; Four Corners Region / Description and travel; Southwest, New / Discovery and exploration / Spanish; Explorers / Southwest, New / Biography; Explorers / Spain / Biography; Discovery and exploration, Spanish; Explorers; Travel; Southwest, New; Spain; United States / Four Corners Region; Biography; Biographies